DAKWAH ISLAM DAN REVOLUSI KOMUNIKASI - Abdullah; Dwi Prasetya, Fiki Febrian (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2023)
The rapid development of information and communication technology has resulted in the emergence of various communication media that have succeeded in breaking through geographical, social, economic, cultural and political boundaries quickly and broadly. This is a feature or characteristic of the communication revolution which provides great opportunities for da'wah actors in an effort to improve the quality of their Islamic da'wah communications. Utilization of good information technology that is balanced with the knowledge and communication skills of effective Islamic da'wa as an effort to convey da'wah messages to the community as recipients of messages is a da'wah strategy that is able to penetrate the wider community. The communication revolution can also be used as a method for conveying Islamic shari'ah with Islamic communication being able to become a filter for society in obtaining information in the media.